Short Communication Screening of Selected Medicinal Plants for the Antioxidant Potential: Short Communication: Antioxidant Potential of Plants (Biological Sciences - PJSIR, 2019)
Screening of selected prominent medicinal plants of Pakistan, used by local herbal practitioners for treatment of various ailments, namely Hyoscyamus niger, Carthamus lanatus, Foeniculum vulgare, Citrullus colocynthis, Cissampelos pareira, Hypericum dyeri, Hypericum perforatum, Equisetum arvense L., Cichorium intybus, Momordica charantia, Solanum xanthocarpum, Galium aparine, Xanthium strumarium, Ammi visnaga and Euphorbia helioscopia, using 2,2-diphenyl picryl hydrazyl (DPPH) radical assay was undertaken. C. pareira, E. arvense L. and C. intybus were found to be devoid of antioxidant activity,  while the rest displayed  variable levels  of antioxidant   potential.